ASPEK YURIDIS PERJANJIAN PENGIRIMAN UANG DENGAN SISTEM ONLINE PADA BANK BRI CABANG TANJUNG BALAI - RUDY FAULAR SEMBIRING (PREMISE LAW JURNAL, 2016)
By the advanced technology followed by the development in administration and communication, anyone can use the services to transfer money from one place to other one. How the importance of the money transfer function for a bank although this is not a main function but its success is a by product that has a role. BRI Bank is one of financial institutions that provide the customer with any services.  The problem in this writing is how the process of money transfer by online system at BRI Bank Branch of Tanjung Balai, what a responsibility of Bank to the losses either to the sender or receiver of the transfer, How the settlement of dispute between the sender of money, receiver of transfer and bank on the dereliction of Bank, what a law consequences of the error in money transfer.; Keywords : Bank, Transaction, Transfer